INFEKTIVITAS MIKORIZA TANAMAN KELAPA SAWIT (Elaeis guinennsis Jack.) YANG TERSERANG GANODERMA - Dian Nur Anisa; Pantja Siwi R Ingesti (Universitas Tidar, 2022)
Palm oil (Elaeis guineensis Jacq.) is an important plantation crop in Indonesia as a producer of vegetable oil and several other derivative products. Palm oil (CPO) production is 47.18 million tons and PKO 4.6 million tons (GAPKI 2019). One of the main obstacles in palm oil cultivation is the presence of biotic stress in the form of Stem Root Disease (BPB) caused by the fungus Ganoderma boninense Pat. is the most harmful disease. In several palm oil plantations in Indonesia, this disease has caused the death of up to 80% or more of the entire population of oil palm plantations.Several factors that influence the development of BPB disease in the field are plant age, soil type, nutrient status and replanting technique. The characteristics of Ganoderma include soil borne, necrotropic and have various means of self-defense, therefore, BPB disease control must be carried out in an integrated manner between the use of resistant palm oil plants, the use of superior biological control agents and technical culture measures.One of the prevention alternatives that can be done is by utilizing soil microbes that can be in symbiosis with palm oil roots, such as Arbuscular Mycorrhizal Fungi (AMF). Mycorrhizae play a role in improving soil health, are environmentally friendly and able to improve soil nutrient status and agricultural products. Therefore, it is necessary to conduct research on the infectivity of mycorrhizae on healthy plants and plants that are attacked by Ganoderma.Keyword : Infectivity, Oil palm, Ganoderma